Analysis of Waste Processing Cost Efficiency in Pangkalpinang City Stochastic Frontier Analysis and Triple Helix Analysis Approaches - Valeriani, Devi; Fitriyanti, Eka; Mulyadi, Edih; Rozi, Rozi; Permadi, Andi; Suprianto, Edy; Maheswara, Perpetua Westri (Fakultas Ekonomi dan Bisnis Universitas Lampung, 2025)
Garbage accumulation in Pangkalpinang City continues to increase every year. This research analyzes the influence of input factors on output and analyzes the efficiency of waste processing in sub-districts in Pangkalpinang City. Then this research will also develop strategies that can be implemented to increase the efficiency of waste processing in sub-districts in Pangkalpinang City. The analysis technique used in this research uses quantitative analysis and qualitative analysis. Quantitative analysis uses stochastic frontier analysis (SFA), while qualitative analysis uses Triple Helix Analysis. The data used is monthly data from 2020 to 2022. This research found that the input factors that influence the efficiency value of waste processing in Pangkalpinang City are not yet appropriate. Then this research also shows that waste processing in Pangkalpinang City is technically efficient. However, there were findings of inefficiency in the model which had an effect of 906555.04 percent. This indicates that there are the most important input factors that should be in the model. Increasing waste processing in Pangkalpinang City is prioritized in the recycling program. The Triple Helix aspect needs to be considered as a priority because it has an impact on the sustainability of increasing waste processing in Pangkalpinang City, so it is necessary to develop a Triple Helix strategy. There are six programs that need to be promoted to stakeholders, namely: guidance, mentoring, guidance/training, funding, technology and information.